(untitled) (Philological Studies, 2019)
The article contains a presentation and a comparative review of recent translations by Toby Garfitt of Prešeren’s Sonnets of Unhappiness. After a close grammatical, semantic and stylistic analysis comparing Garfitt’s to some of the previous translations, the author concludes that these most recent translations are very likely the best, while supposing that one of the possible reasons for their quality may be the fact that the »greatest Slovenian poet« was, in the eyes of the translator, never a »monument« but simply a good poet who can still be read as such in spite of the lapse of two centuries separating the modern reader, Slovenian or English, from his period.